2010
DOI: 10.1007/s13233-010-0806-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties, thermal behavior, and molecular simulations of azo-polysiloxanes under light stimuli. Insight into the relaxation

Abstract: Light-sensitive materials as azo-polymers have interesting applications in microelectronics, biology, or energy storage, due to their capacity to change their supramolecular ordering. Light-induced modifications result in i) changes in the azobenzene-groups dipole moment due to the trans-cis isomerization, ii) thermal backward cistrans relaxation, and iii) re-ordering of the polymer chain conformation. Conjugation of these phenomena leads to mass transport in the solid state, which is still not well understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As shown in Figure S4 in the Supporting Information, the ultraviolet–visible spectra corresponding to Azo–Psi and Azo–PCMS, reflected strong absorption maxima in the domain of 350 nm, which were attributed to the trans–cis isomerization (with the cis–trans absorption being present at 450 nm). As a result, in a microsecond scale time irradiation, a high excess of the cis isomer content was expected and was reported for the trans one (the cis–trans relaxation was less probable in the absence of visible light, with the process taking place in a scale time of hours). The trans–cis isomerization was not accomplished only by an important geometrical azo‐molecule modification but by a significant change in the dipole‐moment value, which increased from 1.6 to 4.5 D .…”
Section: Resultsmentioning
confidence: 76%
“…As shown in Figure S4 in the Supporting Information, the ultraviolet–visible spectra corresponding to Azo–Psi and Azo–PCMS, reflected strong absorption maxima in the domain of 350 nm, which were attributed to the trans–cis isomerization (with the cis–trans absorption being present at 450 nm). As a result, in a microsecond scale time irradiation, a high excess of the cis isomer content was expected and was reported for the trans one (the cis–trans relaxation was less probable in the absence of visible light, with the process taking place in a scale time of hours). The trans–cis isomerization was not accomplished only by an important geometrical azo‐molecule modification but by a significant change in the dipole‐moment value, which increased from 1.6 to 4.5 D .…”
Section: Resultsmentioning
confidence: 76%
“…During the azobenzene isomerization, the wettability of the surface was also modified, as a result of geometry and dipole moment changes. Previous molecular modeling studies [32] evidenced a dipolemoment value for the trans-azophenol of 1.6 D that increases to 4.5 D in the cis configuration. These molecular modeling studies showed the displacement of the azo-groups at the film surface.…”
Section: Resultsmentioning
confidence: 90%
“…The liquid crystalline material has special physical, chemical and optical properties. Azo group is functional group of special optical activity [8][9][10]. If the liquid crystal compounds are combined with the optically active group of azo form.…”
Section: Introductionmentioning
confidence: 99%